Frontispiece: Disentangling Ultrafast Electronic and Structural Dynamics with X‐Ray Lasers. Issue 59 (23rd October 2018) - Collet, Eric; Cammarata, Marco
Abstract : Understanding the elementary processes responsible for ultrafast light‐induced transformations require watching electronic and structural reorganizations on their intrinsic timescales. The X‐ray free electron lasers (X‐FEL) represent a new generation of incredibly short and ultra‐bright X‐ray source, which provide ultrafast probes, sensitive to electronic and structural reorganizations. It is then possible to disentangle electronic and structural dynamics, by identifying various the sequence of electronic states involved and by tracking coherent and incoherent structural dynamics on the femtosecond timescale. Recent studies evidenced how X‐FEL based techniques can help understanding processes responsible for light‐activated functions, and which may occur beyond the Born–Oppenheimer approximation. For more information see the Concept by E. Collet and M. Cammarata on page 15696 ff.